How children reason - Jackson, Stephen
This paper describes three experiments that were used with carefully-chosen samples of normal and educationally sub-normal children from 5 to 15 years, to test the validity of the findings of Piaget and Inhelder on how the ability to reason develops from a stage of pre-logical thought, typical of children below the age of 6-7, to a period when abstract reasoning becomes possible, about the age of 12-13. Although the whole age-range was tested, this article deals only with the reactions of infants and dull juniors, that is, children with mental ages below seven, whose reasoning is pre-logical
Reprinted from ""The Teacher""
Keywords: Children